2004
DOI: 10.1103/physrevlett.92.205006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonlocal Transport on Heat-Wave Propagation

Abstract: We present the first direct measurements of spatially and temporally resolved temperature and density profiles produced by nonlocal transport in a laser plasma. Absolutely calibrated measurements have been performed by Rayleigh scattering and by resolving the ion-acoustic wave spectra across the plasma volume with Thomson scattering. We find that the electron temperature and density profiles disagree with flux-limited models, but are consistent with nonlocal transport modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Recent experiments have shown that f = 0.05 is inappropriate for "open" geometry targets such as gas jets [9] and gas balloons [10]. Nonlocal transport models give good results for these targets.…”
Section: A Electron Thermal Conductionmentioning
confidence: 99%
“…Recent experiments have shown that f = 0.05 is inappropriate for "open" geometry targets such as gas jets [9] and gas balloons [10]. Nonlocal transport models give good results for these targets.…”
Section: A Electron Thermal Conductionmentioning
confidence: 99%
“…Since λ mfp /L < 100, nonlocality can be expected to be important [15]. The steep temperature gradients caused by intense laser heating in a hohlraum have been shown to result in non-local heat flow [16,17]. Careful consideration of the electron population with 2v th < v < 4v th is required as these carry most of the heat.…”
mentioning
confidence: 99%
“…This is often done to treat nonlocal transport in plasmas with low collisionality, in which particle and energy fluxes at a given location are affected by conditions in distant regions of the plasma, which represents an important and complex problem. Often, ad hoc schemes are used in which the flux is simply limited to a fraction of its free-streaming value [1,8,13,[52][53][54]. Data such as presented here can provide a measurement of fluxes and thermodynamic gradients with high temporal and spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increasing mean free path with particle kinetic energy, the situation can already change for mean free path on the order of or longer than 1% of the length scale of plasma gradients [1]. This gives rise to kinetic effects such as streaming plasmas and non-local transport, which are intensely studied because of their importance in many plasma environments, such as high-density laser-produced plasmas [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and astrophysical plasmas like the solar wind [19], solar atmosphere [20,21], solar flares [22], and supernovae [23].…”
Section: Introductionmentioning
confidence: 99%